2014
DOI: 10.3892/ol.2014.2257
|View full text |Cite
|
Sign up to set email alerts
|

Association between four common microRNA polymorphisms and the risk of hepatocellular carcinoma and HBV infection

Abstract: microRNAs (miR/miRNAs) have been demonstrated to function as tumor suppressors and oncogenes, and miRNA polymorphisms may have a role in cancer development. The present study aimed to investigate the association between the miR-146aG>C, miR-149C>T, miR-196a2C>T and miR-499A>G polymorphisms and the risk of hepatocellular carcinoma (HCC) and hepatitis B virus (HBV) infection. A total of 271 patients with HCC and 532 healthy control participants were enrolled in the present study. miR-146aG>C, miR-149C>T, miR-196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…One study in the present meta-analysis did not provide definite criteria for the HCC diagnosis. 36 The genotype distributions of the controls in 3 studies were inconsistent with HWE for miR-146a rs2910164 polymorphism 23 , 24 , 27 and 2 were inconsistent with HWE for miR-196a2 rs11614913 polymorphism. 24 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study in the present meta-analysis did not provide definite criteria for the HCC diagnosis. 36 The genotype distributions of the controls in 3 studies were inconsistent with HWE for miR-146a rs2910164 polymorphism 23 , 24 , 27 and 2 were inconsistent with HWE for miR-196a2 rs11614913 polymorphism. 24 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…For analyses of pooling more than three studies, the significance of ORs was not influenced materially by omitting any single study (data not shown). For the miR-146a rs2910164 polymorphism, sensitivity analysis was further performed by omitting the studies by Shan et al, Kou et al, and Zhou et al 23 , 24 , 27 in which the control populations were not in accordance with HWE. The significance of all ORs was not altered after excluding these 3 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In another independent study they found the T allele in the miR-219-1 promoter to be strongly associated with HBV clearance [ 70 ]. On the other hand, Kou et al [ 71 ] found that the miR-196a2C>T polymorphism imparts protection in HBV-related HCC. Yu et al .…”
Section: Mirna Polymorphism and Hbv Infectionmentioning
confidence: 99%